Cholecystokinin analogs with suppressed central activities - Maletínská, L; Pírková, J; Hlavácek, J; Slaninová, J (Peptides, 1998)
Several analogs of Boc-protected C-terminal heptapeptide of cholecystokinin (Boc-CCK-7) with modified C-end Phe were pharmacologically characterized. The influence of the number of methyl groups on aromatic side chain of Phe was investigated in following tests: binding to pancreatic and brain membrane receptors, gall bladder contraction, amylase secretion, anorexia, sedation and analgesia. Two analogs seem to be promising selective anorectic agents with strongly protracted effect: Boc-[Phe(triMe)7]CCK-7 and Boc-[Phe(pentaMe)7]CCK-7. The first analog exhibits the same spectrum of activities as CCK-8, however partially decreased central effects, the second one shows partially decreased peripheral activities and totally suppressed central ones. Our study supports the idea that C-terminal residue of CCK is more important for biological potency than for binding to CCK receptors.
Keywords: práh bolesti; Rats; Cholecystokinin; spánek; Guinea Pigs; Receptor, Cholecystokinin B; nechutenství; amylasy; hypnotika a sedativa; mužské pohlaví; Central Nervous System; Gallbladder; Rats, Wistar; Sleep; Receptor, Cholecystokinin A; Mice; receptor cholecystokininu B; Eating; krysa rodu Rattus; morčata; žlučník; centrální nervový systém; cholecystokinin; receptor cholecystokininu A; zvířata; Analgesics, Non-Narcotic; Hypnotics and Sedatives; Receptors, Cholecystokinin; receptory cholecystokininu; Amylases; myši; potkani Wistar; Anorexia; Pain Threshold; neopioidní analgetika; přijímání potravy; Male; Animals